Free IGF-1, Intact IGFBP-4, and PicoPAPP-A are Altered in Acute Myocardial Infarction Compared to Stable Coronary Artery Disease and Healthy Controls - Anastasilakis, Athanasios D.; Koulaxis, Dimitrios; Upadhyay, Jagriti; Pagkalidou, Eirini; Kefala, Nikoleta; Perakakis, Nikolaos; Polyzos, Stergios A.; Economou, Fotios; Mantzoros, Christos S. (Hormone and Metabolic Research, 2019)
Insulin-like growth factor-1 (IGF-1) and its binding proteins have been implicated in the pathophysiology of coronary artery disease (CAD) and myocardial infarction (MI). We investigated components of the IGF-1 system in circulation at the time of acute MI and following reperfusion in relation to levels of stable CAD patients and controls. Patients with MI (MI Group, n=31) treated with percutaneous coronary intervention (PCI) were compared to patients with stable CAD subjected to scheduled PCI (CAD Group, n=40) and controls with symptoms mimicking CAD without stenosis in angiography (Control Group, n=43). The number and extent of stenosis were recorded. Total and free IGF-1, total and intact IGF binding protein (IGFBP)-3 and -4, pico-Pregnancy Associated Plasma Protein-A (PAPP-A), and the known markers ALT, AST, CK and CK-MB were measured at baseline and 6 or 24 h after the intervention. Patients with MI had higher free IGF-1 (p=0.003) and PAPP-A (p=0.011), but lower intact IGFBP-4 (p=0.006) compared with patients with stable CAD or healthy controls. None of the investigated molecules changed following reperfusion or correlated with the extent of stenosis. AST (p<0.001), CK (p<0.001) and CK-MB (p<0.001), were also higher. Free IGF-1, intact IGFBP-4 and PAPP-A could predict MI, but with lower accuracy than CK-MB. In conclusion, free IGF-1 levels are higher in MI compared to CAD patients and controls and this could result from increased cleavage of its binding protein IGFBP-4 by the higher PAPP-A levels. Free IGF-1, intact IGFBP-4, and/or PAPP-A are inferior to CK-MB as predictors or markers of myocardial damage.
Keywords: IGF; IGFBP; myocardial infarction; PAPP-A; percutaneous coronary intervention